Computational Insights into the Electronic, Optical, and Reactivity Behavior of Halogenated Phenanthrene Derivatives - Omer, Rebaz A.; Othman, Khdir A.; Azeez, Yousif H.; Qader, Aryan F. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
Abstract—This study explores the complex effects of halogenation on polycyclic aromatic hydrocarbons (PAHs), specifically focusing on phenanthrene. The research aims to understand how the substitution of halogens – namely fluorine (F), chlorine (Cl), and bromine (Br) – in the phenanthrene structure affects its electronic properties, reactivity, and potential applications. The results indicate that halogenation reduces the HOMO-LUMO gap by 0.0100 eV, 0.0064 eV, and 0.2438 eV for F, Cl, and Br, respectively. In addition, it increases the electronegativity (e.g., phenanthrene: 3.6371 eV; phenanthrene-Br: 3.8575 eV), enhancing electron attraction from the phenanthrene rings and lowering the chemical potential. Through detailed analyses of molecular orbitals and density of states, the study reveals significant shifts in energy levels and optical properties. It also employs NMR spectroscopy, potential energy maps, and charge distribution to provide a comprehensive understanding of the compounds. Reduced Density Gradient and Non-Covalent Interaction (NCI) analyses further elucidate the complexities of intermolecular forces in the halogenated derivatives. The research delves into drug-likeness, Natural Bond Orbital (NBO) analysis, and Non-linear Optical properties, highlighting potential applications in medicine, environmental science, and organic electronics. Notably, the halogenated molecules exhibit more intense coloration compared to undoped phenanthrene, with absorption peaks shifting to λ = 295.1 nm for phenanthrene-Cl, 305.3 nm for phenanthrene-F, and 307.2 nm for phenanthrene-Br, compared to λ = 293.0 nm for pure phenanthrene. These findings underscore the transformative impact of halogenation, positioning this study as a significant contribution to the understanding and potential utilization of halogenated PAHs.